Complicaciones agudas post apendicectomía en el tratamiento de apendicitis aguda. - Bonilla Robalino, Cynthia Dayana (2021)
Acute appendicitis continues to be the most common cause of emergency surgery due to its high prevalence in society; biomarkers, current and advanced imaging techniques are used to facilitate its diagnosis and proper management. Nowadays, there are technological advances in surgery, which minimize operative trauma, and they increasingly use potent antibiotics. Several post-operative complications are derived in the treatment of acute appendicitis. The purpose of this research is to develop documentary research based on worldwide and local publications of scientific impact on post-appendectomy complications in the treatment of patients with acute appendicitis through the present documentary bibliographic. This review shows an analysis of 77 scientific articles, selected based on the bibliographic search algorithm, under inclusion and exclusion criteria and respecting the principles of bioethics, for which, based on the results of this research, approximately 20 types of complications can be described, which are classified by their time of immediate, mediate, and late evolution, the same ones that are described in the present work. Therefore, this research shows the need to master knowledge about the natural course of acute appendicitis, timely clinical and surgical management to not compromise the patient with various post complications procedures derived from appendicular pathology.